Astronomy a self-teaching guide - Moché, Dinah L. 1936- (Wiley, 1993)
This edition has been updated completely and features amazing new discoveries and the latest developments such as the Neptune flyby and the Hubble space telescope. It retains the self-instructional format and clear writing style that made it popular.